Transfer of 360° virtual reality and match broadcast video-based tests to on-field decision-making - Kittel, A.; Larkin, P.; Elsworthy, N.; Spittle, M. (Science and Medicine in Football, 2021)
This study aimed to assess the level of transfer of two reliable and valid video modes to in-game decision-making performance. Two video-based tests of 25 clips each (360°VR and match broadcast vision) assessed off-field decision-making accuracy in elite Australian football umpires (n=21). Game performance was assessed across four games for each participant, classified into two groups based on this measure; "highly skilled" or `skilled`. Decision-making was assessed for correct, missed and unwarranted decisions in video-based tests and in-game assessments. Independent t-tests analysed differences between highly skilled and skilled in-game decision-makers for each test. Correlations also compared experience and in-game with video-based test decision-making performance. For both video-based tests, there were no significant differences between highly skilled and skilled in-game decision-makers, nor any significant correlations. Officials who made less unwarranted decisions in-game (highly skilled) made significantly less unwarranted decisions in the match broadcast test. There was a significant correlation between experience and 360°VR correct decision-making. Neither video-based test had the sensitivity to discriminate between elite officials, potentially due to the third-person perspective (match broadcast task) or sub-elite players presented (360°VR). Optimising the representativeness of off-field tasks through including similar constraints to performance environments is an important consideration for researchers and practitioners.